Analysis on Intention of Purchasing Organic Foods by The Undergraduate Students of IPB Using The Theory of Planned Behavior Approach - Heppy Setiawati; Hartoyo Hartoyo; Megawati Simanjuntak (Jurnal Manajemen & Agribisnis, 2018)
This study aims to identify factors that can increase the intention of buying organic foods and its implications in the design of organic food marketing strategy. The main model adopts Theory of Planned Behavior. Six variables were used in this study, namely, health awareness, environmental awareness, attitudes toward organic foods, subjective norms, perceptions of behavior control and organic food purchase intentions. The data to test the research model were collected from 140 respondents and were analyzed using statistical structural equation modeling method. The results of the study indicate that health awareness, environmental awareness, attitudes on organic foods, subjective norms and behavior control perceptions significantly influence the intention of buying organic foods. Furthermore, health awareness and environmental awareness have no significant effects on organic food purchase intention. The results of this study then become the basis in designing strategies to build a positive attitude on organic foods, subjective norms, and perceptions of consumer behavior control of organic foods that is by promoting organic foods through online or on certain events, creating new innovations so that the foods look attractive, and broadening market reach for organic food products to be more easily available.Keywords: purchase intention, organic food, SEM-LISREL, marketing strategic, Theory of Planned Behavior